COVID-19 DI DESA KUTUWETAN KECAMATAN JETIS KABUPATEN PONOROGO - Wiwiek Retti Andriani; Endang Purwaningsih; Fiky Niswati Yuslihah; Dewi Ikhfina Karima (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2022)
PTM-DM cadres have a big role in handling DM in the community. During the Covid-19 pandemic, the role of cadres is very much needed to help DM sufferers to carry out self-care. This is because, during the Covid-19 Pandemic, Posbindu or Prolanis services were not carried out. This community service activity aims to help PTM-DM Si Manis cadres improve their ability to control PTM through education and assistance to cadres about the management of DM patients with the 5 Pillars of DM.